ANALYSIS OF EXISTING CONDITIONS AND FACTORS INFLUENCING THE SUSTAINABILITY OF THE NGUDI LESTARI WASTE BANK IN SEMARANG - Esti Lestari; Budi Warsito; Purnawan Adi Wicaksono (RADJA PUBLIKA, 2025)
Urban waste management is a pressing issue that requires sustainable, community-based solutions. The Ngudi Lestari Waste Bank in Tinjomoyo Village, Semarang City, serves as a participatory model that provides economic, social, and environmental benefits. Thisstudy analyzes the existing conditions and identifies factorsinfluencing the sustainability of the waste bank. A mixed-methodsapproach was employed, including questionnaires from 69 respondents, in-depth interviews with management, stakeholders, customers, and partners, as well as field observations. Quantitativedata were analyzed descriptively using SPSS, while a SWOT analysisidentified strengths, weaknesses, opportunities, and threats. Resultsindicate that the waste bank is in very good condition, with an overallmean of 4.62. The economic (4.62), social (4.59), environmental(4.69), technological (4.62), and institutional governance (4.60) aspects all demonstrate strong performance. Key strengths includeeconomic benefits for members, positive environmental impacts, anda robust organizational structure. Social and technological aspects, while performing very well, still require attention in communityeducation and digital system integration. Supporting factors includeactive community participation, institutional backing, and beneficialenvironmental outcomes, whereas inhibiting factors involve limitedfacilities, fluctuating waste prices, and uneven community awareness.The SWOT analysis suggests that strategies to enhance sustainabilityshould focus on strengthening institutional capacity, digitalizingmanagement systems, and expanding partnerships with educationalinstitutions. Recommended actions include enhancing environmentaleducation programs, implementing a digital waste savings system, andstrengthening policy support. Overall, the Ngudi Lestari Waste Bank effectively contributes to community-based waste management andhas strong potential to serve as a model for sustainable wastemanagement at the local level.